The Vulnerability to Methamphetamine Dependence and Genetics: A Case-Control Study Focusing on Genetic Polymorphisms at Chromosomal Region 5q31.3 - Xiao, Jing; Ma, Yitian; Wang, Xiaochen; Wang, Changqing; Li, Miao; Liu, Haobiao; Han, Wei; Wang, Huiying; Zhang, Wenpei; Wei, Hang; Zhao, Longrui; Zhang, Tianxiao; et al. (Frontiers in Psychiatry, 2022)
Objectives: Methamphetamine (METH) is a central nervous psychostimulant and one of the most frequently used illicit drugs. Numerous genetic loci that influence complex traits, including alcohol abuse, have been discovered; however, genetic analyses for METH dependence remain limited. Increased histone deacetylase 3 (HDAC3) expression has been detected in Fos-positive neurons in the dorsomedial striatum following withdrawal after METH self-administration. Herein, we aimed to systematically investigate the contribution of HDAC3 to vulnerability to METH dependence in a Han Chinese population. Methods: In total, we recruited 1,221 patients with METH dependence and 2,328 age and gender-matched controls. For genotyping, we selected 14 single nucleotide polymorphisms (SNPs) located within ±3 kb regions of HDAC3. The associations between genotyped genetic polymorphisms and the vulnerability to METH dependence were examined by single marker- and haplotype-based methods using PLINK. The effects of expression quantitative trait loci (eQTLs) on targeted gene expressions were investigated using the Genotype-Tissue Expression (GTEx) database. Results: SNP rs14251 was identified as a significant association signal (χ2 = 9.84, P = 0.0017). An increased risk of METH dependence was associated with the A allele (minor allele) of rs14251 [odds ratio (95% confidence interval) = 1.25 (1.09-1.43)]. Results of in silico analyses suggested that SNP rs14251 could be a potential eQTL signal for FCHSD1, PCDHGB6, and RELL2, but not for HDAC3, in various human tissues. Conclusions: We demonstrated that genetic polymorphism rs14251 located at 5q31.3 was significantly associated with the vulnerability to METH dependence in Han Chinese.